Time impact on non-activated and kaolin-activated blood samples in thromboelastography - Durila, Miroslav; Lukáš, Pavel; Bronský, Jiří; Cvachovec, Karel (BMC anesthesiology, 2015)
BACKGROUND: The correct methodology of thrombelastography might be influenced by elapsing time. In our study we investigated kaolin activated citrated samples together with non-activated citrated samples in relation to the elapsed times of 0, 15 and 30 minutes to compare both methods and to find out if there is an impact of time on results of thrombelastography. METHODS: Blood samples obtained from 10 healthy volunteers were analyzed after 0, 15 and 30 minutes from sampling with kaolin activation and without activation. Then the results were analysed and compared between the non-activated and the kaolin-activated method. RESULTS: All blood samples became more hypercoagulable with the time elapsing, both in non-activated and kaolin-activated samples and differences between both groups were found statistically and clinically significant after only 0 minutes. CONCLUSIONS: The non-activated citrated method seems to be reliable and suitable for thrombelastography in non-emergency cases (planned surgical procedures) when we have time to wait 15-30 minutes to get results. In urgent situations a rapid thrombelastography test should be preferred. Although the kaolin-activated method can also be used, results must be interpreted with caution.
Keywords: citráty; časové faktory; Blood Specimen Collection; analýza rozptylu; Kaolin; zdraví dobrovolníci pro lékařské studie; koagulancia; Analysis of Variance; kaolin; Citrates; Coagulants; lidé; Healthy Volunteers; Humans; Thrombelastography; Time Factors; odběr vzorku krve; tromboelastografie